(untitled) (Research, Society and Development, 2021)
Objectives: To assess the knowledge level on euthanasia, orthothanasia and dysthanasia among medical students at universities in Aracaju; to analyze whether knowledge on euthanasia, dysthanasia and orthothanasia has been improved over the years in medical courses and to verify whether medical students agree/disagree with the practices of euthanasia, orthothanasia and dysthanasia. Methodology: Exploratory, descriptive, cross-sectional and quantitative study; produced through a questionnaire applied to medical students at two universities in Aracaju. Data analyzed with descriptive statistics and significance level set at p <0.05. Results: 222 medical students participated (51% from public and 49% from private universities). Of these, 19% did not know how to define orthothanasia, 7% euthanasia and 17% dysthanasia. It was observed that from the 10th to the 12th period 15% knew how to define euthanasia, 15% dysthanasia and 16% orthothanasia. On approval, 54% approved of euthanasia, 74% of orthothanasia and 43% approved of dysthanasia without knowing its concept. Final considerations: Medical graduation is incipient in this issue, as a wrong definition is a basic indication of destructuring, causing daily unpreparedness. Agreeing/disagreeing with practices is influenced by knowledge, thus, almost half of the students approved dysthanasia without knowing its meaning, increasing the probability of future medical error, malpractice or other serious infractions. There is a decrease in correct answers for students who are about to graduate, showing that there are no interventions to improve knowledge throughout college. Including bioethical subjects about euthanasia, dysthanasia, orthothanasia and death process, and acting opportunities, indicate a good start in the interventions required.